Municipal sludge as soil amendment for flower crop growth: Insights into the current situation and potential challenges - Amrin, B A; Swarnapriya, R; Ganga, M; Suresh, S; Parameswari, E; Meenakshi, P (Plant Science Today, 2025)
The utilization of treated municipal sludge or biosolids, as an organic soil enhancer has garnered significant interest for its potential to enhance soil quality and plant growth. The use of treated sludge as an amendment is seen as a viable method for waste disposal and soil improvement. The impact of sludge applications on soil properties, microbiome and flower crop growth and yield depends on factors such as sludge composition, application rates and specific plant species. Safety concerns regarding contaminants such as heavy metals, pathogens and organic pollutants have raised questions about practical application, especially in flower crop cultivation. Despite its potential benefits, challenges like insufficient infrastructure, regulatory awareness and risks of improper handling hinder widespread adoption of municipal sludge as a flower crop soil amendment. Yet, ensuring proper treatment processes and adherence to regulatory guidelines is vital to mitigate potential risks. This review provides an overview of the current status and potential challenges related to the usage of municipal sludge as a soil amendment for flower crops. Addressing these challenges necessitates enhanced sludge management, infrastructure investment and sustainable integrated strategies. Continuous research is crucial to optimize treatment, create value-added products and understand long-term impacts of sludge on soil and environmental sustainability in flower crops.